2013
DOI: 10.1186/2049-6958-8-61
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and carotid intima-media thickness in chronic obstructive pulmonary disease

Abstract: BackgroundThe aim of this study is to investigate the prevalence of metabolic syndrome (MetS), carotid intima media thickness (IMT), and serum C-reactive protein (CRP) levels in patients with chronic obstructive pulmonary disease (COPD), and the possible relationships among them.MethodsFifty stable COPD patients and 40 healthy controls were included in the study. The participants were further divided into four groups according to their smoking status. Pulmonary function tests were performed in COPD patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Additionally, CIMT was found to be significantly higher among our study COPD patients than the controls (0.85±0.18 mm vs. 0.63±0.076 mm, p<0.001). These results coincide with the results of other studies in the literature (4,17,(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, CIMT was found to be significantly higher among our study COPD patients than the controls (0.85±0.18 mm vs. 0.63±0.076 mm, p<0.001). These results coincide with the results of other studies in the literature (4,17,(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 83%
“…30 One of our previous studies suggests that IH may cause the increase of IMT, 6 and there is substantial evidence that IH in rodents plays a specific role in promoting cellular changes at the vascular wall, thus triggering atherosclerosis. 30,31 Furthermore, Ozgen Alpaydin et al 32 observed increased C-IMT in patients with COPD compared with controls after adjusting for smoking, hypertension, fasting plasma glucose, triglyceride, and high density lipoprotein cholesterol levels. This finding might suggest that patients with air flow obstruction are more prone to atherogenesis due to some other mechanisms apart from smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might suggest that patients with air flow obstruction are more prone to atherogenesis due to some other mechanisms apart from smoking. 32 This emphasizes the importance of timely diagnosis and treatment of coexistent COPD and OSA for preventing the development of severe cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of male patients was significantly lower in the MetS group compared to the non-MetS group. Furthermore, four studies reported higher serum C-reactive protein (31,(34)(35)(36) and serum interleukin-6 (31) in COPD patients with MetS compared with patients without MetS (data not shown).…”
Section: General Characteristics Of Copd Patients With Mets and Withomentioning
confidence: 99%
“…In total, 10 studies compared COPD patients (n = 2864) with a control group (n = 24532) (25,30,34,(36)(37)(38)(39)(40)(41). Characteristics of COPD patients are shown in Table 2, characteristics of the controls are presented in Supplemental Table S1.…”
Section: Differences In Prevalence Of Mets and Its Components Betweenmentioning
confidence: 99%